Axonal dysfunction is associated with interferon-γ levels in childhood-onset systemic lupus erythematosus: a multivoxel magnetic resonance spectroscopy study. (20th July 2021) - Frittoli, Renan Bazuco; Pereira, Danilo Rodrigues; Lapa, Aline Tamires; Postal, Mariana; Sinicato, Nailu Angelica; Fernandes, Paula Teixeira; Cendes, Fernando; Castellano, Gabriela; Rittner, Leticia; Marini, Roberto; Niewold, Timothy B; Appenzeller, Simone
Abstract: Objective: Axonal/neuronal damage has been shown to be a pathological finding that precedes neuropsychiatric manifestations in SLE. The objective of this study was to determine the presence of axonal dysfunction in childhood-onset SLE patients (cSLE) and to determine clinical, immunological and treatment features associated with its occurrence. Methods: We included 86 consecutive cSLE patients [median age 17 (range 5–28) years] and 71 controls [median age 18 (5–28) years]. We performed proton magnetic resonance spectroscopic imaging using point resolved spectroscopy sequence over the superior–posterior region of the corpus callosum and signals from N -acetylaspartate (NAA), choline-based (CHO), creatine-containing (Cr), myo -inositol (mI), glutamate, glutamine and lactate were measured and metabolites/Cr ratios were determined. Complete clinical, laboratory and neurological evaluations were performed in all subjects. Serum IL-4, IL-5, IL-6, IL-10, IL-12, IL-17, TNF-α and INF-γ cytokine levels, antiribosomal P protein antibodies (anti-P) and S100β were measured by ELISA using commercial kits. Data were compared by non-parametric tests. Results: NAA/Cr ratios ( P = 0.035) and lactate/Cr ratios ( P = 0.019) were significantly decreased in cSLE patients when compared with controls. In multivariate analysis, IFN-γ levels [odds ratio (OR) = 4.1; 95% CI: 2.01, 7.9] and depressive symptoms (OR = 1.9; 95% CI: 1.1, 3.2) were associated with NAA/Cr ratio. Increased CHO/Cr was associated with the presence of cognitive impairment (OR = 3.4; 95% CI: 2.034, 5.078; P < 0.001). mI/Cr ratio correlated with cumulative glucocorticoids dosage ( r = 0.361, P = 0.014). Conclusion: NAA and CHO ratios may be useful as biomarkers in neuropsychiatric cSLE. Longitudinal studies are necessary to determine whether they predict structural damage.